A influência da postura corporal no movimento de alcance manual em lactentes de 4 meses de vida. - Carvalho, Raquel de Paula (2004)
The aim of this work was to investigate the influence of body posture during reaching movements in four healthy, four-month-old infants. Experimental conditions consisted of presenting two toys alternately, at the infant s midline and shoulder levels and midway between the infant s shoulder and wrist. After the reaching, the toy was taken away and given back again for a period of two minutes (for each toy) or until the infant reached for it a total of ten times. This procedure was repeated at the supine posture (0º), a reclined posture (45º) and a sitting posture (70º). We randomized this order these positions. The results were recorded on video and analyzed using the Dvideow system for the purpose of checking the kinematics of the angle of the shoulder (flexion/extension and abduction/aduction) and elbow flexion/extension). Also, we analyzed the rectitude index (the distance traveled by the hand during a reaching movement divided by the distance between the starting and the end points), time (in seconds) in each of the three positions, as well as the frequency of reaching unimanually and bimanually. The statistical method used for the rectitude index was t-Student test and for the frequency of reaching was the analysis of variance (ANOVA). From the results showed that there were differences between the frequency of reaching unimanually and bimanually (p-value=0,0341) in sitting posture. The frequency of reaching was more in sitting posture than in supine posture. In relation to the rectitude index, the test showed a significant difference between the supine and reclined postures (p-value=0,001) and the supine and sitting postures (p-value=0,001). The infants spent the same time reaching in the tree postures. When analyzing the angles, only two babies used the same movement pattern for the three positions. We concluded that, the age of 4 months, reaching does not follow a stable pattern, which can be modified by the position of the infant. Each infant has its own intrinsic dynamics and reacts in different ways to the environmental restrictions imposed by different body positions.